Preparation of Rat Gingival Mitochondria with an Improved Isolation Method - Noriaki Kaneko; Tetsuya Rikimaru; Tetsuyuki Fujimura; Shigeyasu Mori; Saburo Hidaka; Hidehiro Kaya (Hindawi Limited, 2010)
In order to establish a method of obtaining rat gingival mitochondria (Mt), Mt fractions were prepared in various combinations of homogenizing time with collagenase concentration. Rat gingival tissues were excised, minced, treated with collagenase, homogenized, and subjected to differential centrifugation rates. Both the respiratory control ratio (RCR) and adenosine diphosphate/oxygen (ADP/O) ratio of the Mt fraction prepared in a combination of 40, 50, or 60 sec homogenization with collagenase in a concentration range of 0.115%-0.130% (w/v) were measured. The values for the RCR and ADP/O ratio of the Mt fraction obtained in an optimal condition was 1.80±0.05 and 1.65±0.03, respectively. These results suggest that Mt of fairly high quality can be obtained through this refined combination of the homogenizing time and collagenase concentration.